Effect of Narrative Nursing Intervention Based on Targeted Nursing Intervention on Anxiety and Nursing Satisfaction of Patients with Malignant Tumors Undergoing Chemotherapy. (1st December 2021) - Xu, Huixia; Xu, Guoping; Liu, Ying; Mu, Xuejing; Liu, Yang; Hu, Haiping
Abstract : Objective . To explore the effect of narrative nursing intervention based on targeted nursing intervention on anxiety and nursing satisfaction of patients with malignant tumors undergoing chemotherapy. Methods . 120 malignant tumor patients treated with chemotherapy in our hospital from January 2019 to January 2020 were selected as the research objects and randomly divided into group A and group B, with 60 cases in each group. The targeted nursing intervention was performed to group B, and the targeted nursing intervention centering on narrative nursing was performed to group A, so as to compare their distress thermometer (DT) scale scores, depression and anxiety scale scores, Medical Coping Modes Questionnaire (MCMQ) scores, Functional Assessment of Cancer Therapy-General (FACT-G) scores for quality of life, and nursing satisfaction. Results . After nursing intervention, group A obtained 5.00 ± 1.20 points in the DT score, which were significantly lower than group B (P < 0.05 ); and group A achieved significantly lower depression and anxiety scale scores (P < 0.001 ), better MCMQ scores (P < 0.05 ), and higher FACT-G scores (P < 0.05 ) and nursing satisfaction (P < 0.05 ) than group B. Conclusion . The targeted nursing intervention based primarily on narrative nursing can greatly reduce negative emotions, alleviate anxiety, and improve confidence in treatment and quality of life for malignant tumor patients undergoing chemotherapy, with higher nursing satisfaction, which should be promoted and applied in the practice.